PENGARUH STRUKTUR KEPEMILIKAN DAN DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BEI TAHUN 2011–2013) - Laurensia Chintia Dewi; Yeterina Widi Nugrahanti (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2014)
The objective of this study is to examine the influence of management ownership, institutional ownership and board of independent commissioners on firm value. This study focus on consumer goods companies listed in Indonesia Stock Exchange in 2011 until 2013. Firm value in this study proxied by Tobin’s Q. Sampling techniques in the study conducted by purposive sampling technique. A total of 36 the consumer goods companies used as a sample. The technique of analysis of this study used multiple regression. The results of this study indicate that the variable that affect the firm value is board of independent commissioners. While variables that did not affect the firm value is management ownership and institutional ownership.Keywords: Firm value, management ownership, institutional ownership and board of independent commissioners.